Assessing Changes in Insurance Status and Access to Care Among Patients Attending Chicago Sexually Transmitted Infection Specialty Clinics From 2013 to 2019. Issue 3 (1st March 2023) - Korban, Colin; Tabidze, Irina; Broussard, Dawn; Cruz, Yvonne; Kern, David; Mehta, Supriya D.
Abstract : A multiyear survey at Chicago sexually transmitted infection clinics observed increased insurance coverage among patients after the Affordable Care Act implementation, although this did not correlate with increased primary care access, highlighting continued safety net need. Abstract : Background: Public sexually transmitted infection (STI) clinics are safety net providers for uninsured and underinsured individuals but are at risk for closure due to declining budgets and shifting priorities. This study sought to assess changes in insurance status and access to preventive care among public STI clinic patients after immediate and long-term implementation of the Affordable Care Act (ACA). Methods: Patients receiving care in STI clinics administered by Chicago Department of Public Health were asked to complete an anonymous survey in 2013, 2014, and 2019. We estimated the prevalence rate ratio (PRR) of (1) being insured and (2) having access to preventive care over time, adjusted for age, race, and gender/sexual orientation, and employment status. Results: Among 1711 respondents, compared with 2013 patients, patients were 1.41 (adjusted PRR [aPRR]) times more likely to report being insured in 2014 (95% confidence interval, 1.11–1.77) and 1.24 (aPRR) times more likely to report being insured in 2019 (95% confidence interval, 0.99–1.55). After adjusting for other significant variables (age, sex and orientation, and insurance status), reported access to preventive care increased by 34% among respondents in 2019 as compared with 2013 (aPRR, 1.34). Unsurprisingly, being insured was associated with increased preventive care access (aPRR, 1.78). Conclusions: Even after the implementation of the Affordable Care Act, a survey of public STI clinic patients in Chicago found a sizeable proportion of individuals without insurance, and many lacked access to preventive care, highlighting the continued need for these safety net clinics to provide STI care.